I Triennal de Dibuix Joan Miró. - Fundacio Joan Miro, Barcelona (Barcelona : Fundacio Joan Miro, 1989)
Aguilar, Sergi ; Bächli, Silvia ; Badiola, Txomin ; Barceló, Miquel ; Boehle, Hilmar ; Brandl, Herbert ; Cage, John ; Cahn, Miriam ; Camps, Pep ; Condo, George ; Damisch, Gunter ; G. Dokoupil, Jiri ; Dorner, Helmut ; Frangella, Luis ; Gomez, Maria ; Gonzalez, Curro ; Guzman, Federico ; Hanimann, Alex ; Hernandez-Pijuan ; Irazu, Pello ; Kiecol, Hubert ; Kippenberger, M. ; Lacasa, Roser ; Lapa, Alvaro ; LeWitt, Sol ; Lootz, Eva ; Martins, Jorge ; Meuser ; Nauman, Bruce ; Partenheimer, J. ; Penck, A.R. ; Perrin, Carmen ; Proença, Pedro ; Saiz, Manuel ; Serra, Richard ; Shapiro, Joel ; Sicilia, J.M. ; Smith, Ray ; Therrien, Robert ; Trockel, R. ; Urzay, Dario ; Uslé, Juan ; Vélez, Patricio ; Zitko, Otto
I Triennal de Dibuix Joan Miró, Fundacio Joan Miro, Barcelona, 15 de juny - 10 de setembre de 1989
boek